The formation of an aesthetic taste as the most important component of art-pedagogical education - T.P. Reshetnikova; T.D. Furdak (Academy of Cognitive and Natural Sciences, 2007)
The questions of formation of aesthetic taste as an important component of art-pedagogical education based on the main points of the monograph by N. Kalashnik «Aesthetic tastes: their cources andformation».